Metabolic Dysregulation in Polycystic Ovary Syndrome: The Central Role of Insulin Resistance and Novel Therapeutic Perspectives - Nia Ayuni Putri (Asosiasi Dosen Muda Indonesia, 2026)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder with complex reproductive and metabolic consequences that are often not fully addressed by symptom-oriented management strategies. Increasing evidence shows that metabolic dysfunction, particularly insulin resistance and hyperinsulinemia, plays a central role in the pathophysiology of PCOS and contributes to both reproductive and systemic abnormalities. Objective: This study aimed to review and synthesize recent evidence on the metabolic basis of PCOS, with particular emphasis on the role of insulin resistance and hyperinsulinemia as key mechanisms underlying metabolic and reproductive disturbances. Method: This study used a narrative review design by analyzing recent peer-reviewed literature related to insulin signaling disturbances, mitochondrial dysfunction, oxidative stress, inflammatory pathways, and emerging therapeutic approaches in PCOS. The selected studies were examined descriptively to identify major pathophysiological patterns and current treatment perspectives. Findings: The review found that insulin resistance and hyperinsulinemia are major drivers of PCOS across various phenotypes, including non-obese women. Mitochondrial dysfunction and chronic inflammation were also shown to aggravate metabolic and reproductive impairments. In addition, the findings indicate that improvements in metabolic parameters do not always correspond to normalization of reproductive hormones, highlighting the heterogeneous and multifactorial nature of PCOS. Implications: These findings have important implications for clinical practice by supporting the development of personalized and mechanism-based management strategies that integrate metabolic profiling with reproductive goals. Such an approach may improve the effectiveness of long-term treatment and patient outcomes. Originality: The originality of this review lies in its integrative metabolic–reproductive framework, which brings together recent mechanistic insights and emerging therapeutic perspectives to reconceptualize PCOS as a systemic metabolic–reproductive disorder rather than a purely reproductive condition.